Green peach aphid infestation induces Arabidopsis PHYTOALEXIN-DEFICIENT4 expression at site of insect feeding - Louis, Joe (Landes Bioscience, 2012)
The Arabidopsis thaliana PHYTOALEXIN-DEFICIENT4 (PAD4) protein, which has homology to lipases, is required for phloem-based resistance against the green peach aphid (GPA; Myzus persicae Sülzer). PAD4 modulates antibiotic and antixenotic defenses against GPA. PAD4 in conjunction with its interacting partner ENHANCED DISEASE SUSCEPTIBILITY1 (EDS1) also functions in basal resistance to bacterial and oomycete pathogens by promoting salicylic acid (SA)-dependent and SA-independent defenses. By contrast, neither EDS1 nor SA is required for PAD4-controlled defense against GPA. Distinct molecular activities of PAD4 are involved in different aspects of Arabidopsis defense against GPA and pathogens. Histochemical analysis of plants containing a PAD4(p):GUS chimera, which expresses the GUS reporter from the PAD4 promoter, indicated strong PAD4 promoter activity at the site of penetration of the vasculature by the insect stylet. GUS activity was also observed in non-vascular tissues of GPA-infested leaves, thus raising the possibility that a combination of distinct PAD4 activities in vascular and non-vascular tissues contribute to Arabidopsis defense against GPA.